Child safety on various bicycle-mounted seats during vehicle impact - Ptak, Mariusz; Wilhelm, Johannes; Sawicki, Marek; Rusiński, Eugeniusz (Transport, 2019)
This research addresses an important gap in the state of the art by investigating the safety of vulnerable road users – children transported on bicycle seats. The article focuses on three forms of bicycle-mounted child seats and their kinematics during an accident scenario involving a motor vehicle. The front, rear-frame and rear-rack mounted child seat mounting configurations were considered in this study. The research covers the impact of a sports sedan vehicle against a bicycle equipped with the child seat. The assessment of the child safety was done through numerical simulations by coupling the codes of MADYMO and LS-DYNA. The after-impact kinematics for various baby carriers is presented with the emphasis on child’s head and neck injuries. The results were compared to the full-scale test available in the literature. The findings prove a low protection level for the child provided by the bicycle carriers in all considered cases. The study is further devoted to directions of increasing child safety in this means of transportation.First published online 18 March 2019